Building Resilient Micro-Small Enterprises: A Case Study of MSEs In The Midst of The Covid-19 Pandemic - Iwan Donal Paska Manurung; Eko Widodo (Jurnal Administrasi Bisnis, 2022)
The pandemic has affected various sectors of life. The pandemic has attracted the attention of many parties to assess the impacts that arise outside of health impacts, one of which is the impact on micro and small enterprises (MSEs). The central role of MSEs in the national economy is the primary driver of research on how MSEs build resilience in times of crisis. This study focuses on the strength of MSEs during the Covid-19 pandemic. MSEs are the mainstay of the national economy. Therefore, various aids for the recovery of MSEs have become the focus of national economic recovery throughout the world, including Indonesia. This study uses quantitative and qualitative methods on MSEs that are still able to maintain their continuity to this day. This research focused on revealing several characteristics of MSEs’ resilience according to the number of workers, income trends, and the extent to which individual resilience affects organizational resilience. The analysis also revealed a process-based model of how MSEs builds resilience during this ongoing crisis.